A laboratory study on the drag force distribution within model forest canopies in turbulent shear flow - Hsi, George, author; Nath, John H., author; College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1968)
The objective of this study was to determine the distribution of the tree drag force within various model forest canopies subjected to various ambient wind conditions. Ultimately this information may be related to diffusion within the forest canopy. The influence on individual tree drag due to neighboring trees was investigated by arranging the trees in various configurations of columns and rows, the columns being parallel to the ambient wind and the rows being perpendicular. Two tree spacings for the columns and rows were investigated. Furthermore, a large forest canopy field was investigated that covered an area of twenty-one square meters. For this arrangement it was determined that the tree drag field can be classified into two zones - an initial zone and a steady decay zone. In order to study the influence of the boundary layer development on tree drag, the various arrangements of trees were tested under a thin boundary layer condition and under a thick boundary layer condition. In the course of this study a strain gage force dynamometer was developed that can reliably measure a drag force as small as 0.1 gram on a model tree.
CER67-68GH-JHN50.
March 1968.
Prepared under U.S. Army Research Grant DA-AMC-28-043-65-G20 U.S. Army Material Command Washington 25, D.C.
Keywords: Drag (Aerodynamics); Fluid mechanics; Boundary layer control